(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Emergency triage is a critical process in emergency care, requiring collaborative decision-making between paramedics and nurses to effectively prioritize patients based on the severity of their condition. This article explores the dynamic interplay between paramedics and nurses during the triage process, highlighting the importance of clear communication, mutual respect, and shared decision-making. Through case studies and best practices, it elucidates the key principles and strategies that facilitate efficient and accurate triage, ultimately improving patient outcomes in emergency settings.